Exercise-based interventions for ankylosing spondylitis - Salem Alaffari, Naif; Alqahtani, Faisal Ali; Alhudiry, Saeed Ahmed; Alharthi, Nada Marwa; Melibari, Ghaidaa Malik; Alessa, Fatima Ismail; Khan, Abdulrahman Anis; Alanzi, Yousif Bader (International Journal Of Community Medicine And Public Health, 2024)
Ankylosing spondylitis (AS) is a chronic inflammatory condition primarily affecting the axial skeleton, leading to pain, stiffness, and reduced spinal mobility. Exercise-based interventions have emerged as an essential non-pharmacological approach to managing AS, complementing pharmacological treatments. Aerobic exercises, such as swimming and cycling, contribute to cardiovascular fitness while alleviating inflammation and fatigue. Strength training addresses muscle imbalances, enhances postural stability, and prevents further functional deterioration. These benefits are amplified when aerobic and strength exercises are combined, providing comprehensive improvements in mobility, physical function, and overall health. Flexibility exercises, including stretching routines and yoga, play a critical role in maintaining spinal mobility and mitigating the effects of spinal fusion. These interventions target the axial skeleton and surrounding musculature, improving range of motion and reducing stiffness. Innovative modalities such as aquatic therapy further enhance flexibility by minimizing joint stress while promoting effective movement. Tailored exercise programs designed to meet the specific needs of AS patients optimize outcomes by addressing individual limitations and disease severity. These programs integrate various exercise modalities, ensuring sustained physical and psychological benefits. Supervised sessions, group activities, and emerging technologies like teleconsultations enhance adherence and accessibility. Furthermore, the integration of relaxation techniques and mindfulness within exercise regimens provides additional mental health advantages. The holistic benefits of exercise extend beyond physical improvements, addressing psychological challenges such as depression and anxiety often associated with chronic diseases. By maintaining mobility, alleviating pain, and enhancing quality of life, exercise-based interventions underscore the importance of an interdisciplinary approach in managing AS. Ongoing research continues to refine these strategies, highlighting their potential in reducing disease burden and improving long-term outcomes for individuals with AS.